Football fans in the context of negative identity - A.Kutomanov, S. (2019)
The article deals with the issues, related to the existence of such a phenomenon of modern times as football fanaticism. The author analyzes the features of sports rooting, in general, and football fanaticism, in particular. The classification of football fans was proposed, and their main characteristics were described. Social markers, having an impact on the fan’s life and the existence of the fan group, were determined in the context of negative identity. The role of the phenomenon of football fanaticism in modern culture was considered in the article